Effect of Regional Original Income, Revenue Sharing Fund, and Special Allocation Fund for Capital Expenditure and Its Impact on Economic Growth in the District and City in East Kalimantan - Lucky Fajar Prasetyo; Muhammad Saleh; Jiuhardi Jiuhardi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze and determine effect of regional original income, revenue sharing fund, and special allocation fund for capital expenditure and its impact on economic growth in the District and City in East Kalimantan. This research is quantitative descriptive. The data used is secondary data. Secondary data is data obtained from reports on audit results by the Supreme Audit Agency of the Republic of Indonesia Representative of East Kalimantan Province from 2011 to 2020 and the Central Statistics Agency of East Kalimantan Province. The method of analysis used multiple linear regression analysis and path analysis. The results of the study show that regional original income, revenue sharing fund, and special allocation fund directly have a significant effect on capital expenditure. Regional original income, special allocation fund, and capital expenditure directly have a significant effect on economic growth. Revenue sharing fund directly has a unsignificant effect on economic growth. Regional original income, revenue sharing fund, and special allocation fund indirectly have a significant effect on economic growth through capital expenditure.